Efektifitas Media Pembelajaran Berbasis Video Dalam Mengembangkan Minat Siswa Terhadap Penbelajaran Seni Budaya - Anne Effane; Helmia Tasti Adri (THE JOER: Journal Of Education Research, 2022)
Arts and culture learning not only learn about materials related to cultural arts, but also trains students' skills in applying the art materials that have been learned. Therefore, it takes enthusiasm and creativity of students to achieve effective and efficient learning outcomes of art and culture. The main problem in this study is how effective the use of video-based learning media in teaching arts and culture is, what benefits can be obtained by using the media, and what are the obstacle factors that can affect the use of these learning media. This study uses a qualitative approach and has a descriptive nature. Data analysis was carried out by sorting data, presenting data, and finally drawing conclusions. The results of research on the use of video-based media in learning arts and culture in schools using audio-visual media such as computers, laptops, projectors, and others can make the learning atmosphere in the classroom more qualified, teachers and students can also more easily convey and absorb the material presented. being studied by showing interesting and easy-to-understand shows. In addition, video-based learning media is considered more capable of increasing students' enthusiasm and creativity in learning arts and culture. On the other hand, there are also obstacles in the use of audio-visual-based media in the process of learning arts and culture in schools, namely poor maintenance of facilities, and lack of supervision in the use of audio-visual media so that sometimes there is a lot of damage to facilities.